Design of a New Whole Merozoite Vaccine for Malaria - Cai, Mingwei; Wu, Suyu; Zhang, Yuwei (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Malaria is one of the most fatal diseases in the sub-Saharan area, causing more than 200 million people infected and more than 600000 people dead every year. The whole society are working together to develop vaccine to prevent people from being infected. This research will focus on a new whole merozoites vaccine which contains CRISPR-Cas9 based CyRPA protein deficient merozoites. The vaccine is designed to prevent the merozoites from entering the red blood cells so it can stay in the blood, be exposed the immune system and stimulate immune response. This new vaccine can provide a durable and effective prophylactic effect if successful. The vaccine is expected to have no serious and fatal side effects and will undergo animal tests and voluntary tests to test its effectiveness. Further research will focus on resolve the remaining challenges of the vaccine, including red blood cell deformation and the possibility of merozoites still entering the blood cells.